The art of consultative selling in IT taking blue ocean strategy a step further - Upadrista, Venkatesh (Productivity Press Book, 2015)
Companies can succeed not by battling competitors, but rather by creating "blue oceans" of uncontested market space. These strategic moves create a leap in value for the company, its buyers, and its employees, while unlocking new demand and making the competition irrelevant. This book defines an approach on how one can create Blue Oceans and be recognized as a 'Consultative Seller